Overview of nanocellulose as additives in paper processing and paper products - Li Ao (De Gruyter, 2021)
The rapid economic growth and environmental concerns have led to high demands on paper and paper-based products in terms of variety, quantity, quality, and specialty. Enhancement and functionalization with additives are constantly required. Moving away from traditional petroleum-based additives, researchers have attempted to use “green” nanoadditives by introducing renewable environmentally friendly nanocellulose. This article studies the functions of nanocellulose as bio-additives (enhancer, retention and filtration reagent, and coating aid) in paper and paper products, and overviews the research development of nanocellulose-based additives and their applications in the paper industry for both efficient production and paper functionalization. The review shows that (1) a variety of nanocellulose-based bioadditives have been reported for various applications in paper and paper-based products, while commercially viable developments are to be advanced; (2) nanocellulose was mostly formulated with other polymer and particles as additives to achieve their synergistic effects; (3) major interests have concentrated on the nanocellulose in the specialty papers as representing more value added products and in the efficient utilization of recycled fibers, which remains most attractive and promising for future development. This report shall provide most useful database information for researchers and industries for paper recycling and enhancement, and paper-based products innovation and application.